Deciphering the role of IL17RA in psoriasis and chronic mucocutaneous candidiasis: shared pathways and distinct manifestations - Kadhi, Ayat; Eid, Edward; Massaad, Michel J.; El-Rassy, Inaam; Khoury, Dana Maria; Shimomura, Yutaka; Rubeiz, Nelly; Kurban, Mazen; Nemer, Georges (Frontiers in Immunology, 2025)
IntroductionPsoriasis and chronic mucocutaneous candidiasis (CMC), although distinct in their clinical manifestations, often coexist within specific patient cohorts. Despite this intriguing clinical observation, their genetic etiologies have been studied separately, neglecting the shared inflammatory mediator, interleukin 17A-F (IL17A-F). Consequently, the immunogenetic foundations underlying these conditions have remained enigmatic.MethodsIn this study, we analyzed the case of a 5-year-old female born to consanguineous parents who presented with concomitant psoriasis and CMC phenotypes. Utilizing whole exome and transcriptomic sequencing, we meticulously investigated the genetic underpinnings and molecular pathways underlying these complex pathologies. RNA sequencing was performed on a skin biopsy to confirm transcriptomic profiles associated with these conditions.ResultsWe identified a novel bi-allelic variant (NM_014339.6, c.1173C>G A) within the interleukin 17 receptor type A (IL17RA) gene, resulting in a premature stop codon (p. Tyr391Ter). Despite the truncation, our investigations revealed that this variant produces a fully functional IL17RA protein. This was evident from the presence of IL17RA in the patient’s peripheral blood mononuclear cells (PBMCs) and the ability of the mutant IL17RA to dimerize with both wild-type protein and its partners IL17RC and IL17RD. Transcriptomic analysis of the skin biopsy showed a distinct psoriasis-associated signature intertwined with inflammatory pathways, including responses to fungal infections.DiscussionThis report unveils an unprecedented genetic link serving as a common denominator for psoriasis and CMC. The novel IL17RA variant highlights the pivotal role of this receptor in the shared inflammatory pathways underlying these conditions. Our findings bridge a critical knowledge gap and provide insights into the molecular mechanisms connecting these diseases. This discovery not only advances our understanding of their pathophysiology but also lays the groundwork for personalized therapeutic strategies, heralding a new era of precision medicine for patients with intertwined psoriasis and CMC.